Transformasi Pelayanan Digital Melalui Layanan Si Intan BPMP NTB Dalam Pengelolaan Pengaduan Sistem Penerimaan Murid Baru (SPMB) - Khaeroniq Zaennurain; Tri Rahayu; Putri Jasmine; Maula Desti Siltania; Muhammad Khalilurrahman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Digital transformation in public services has become one of the government's strategic efforts to improve service quality by making it more effective, transparent, and responsive. The West Nusa Tenggara Center for Education Quality Assurance (BPMP NTB) developed Si INTAN as a digital information and complaint service to support the implementation of the Student Admission System (SPMB). This study aims to (1) describe the complaint management mechanism of SPMB through the Si INTAN service at BPMP NTB; (2) analyze the extent to which digital service transformation through Si INTAN enhances transparency, responsiveness, and public satisfaction; and (3) identify the challenges and supporting factors in implementing Si INTAN as a digital complaint management instrument in West Nusa Tenggara Province. This study employed a descriptive qualitative approach using in-depth interviews and a literature review for data collection. The research informants consisted of the SPMB coordinator and the technical administrator of Si INTAN at BPMP NTB. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that the complaint management mechanism through Si INTAN is conducted systematically, beginning with the submission of complaints via the official website, followed by verification and clarification by the responsible officers, and ending with the provision of appropriate solutions in accordance with established procedures. The implementation of Si INTAN has improved service accessibility, information transparency, and responsiveness in handling public complaints, enabling the public to access services without visiting the BPMP NTB office directly. However, several challenges remain, including varying levels of digital literacy, limited internet connectivity in certain areas, and the need for continuous public outreach. Therefore, strengthening digital infrastructure, enhancing human resource capacity, and expanding public awareness initiatives are essential to optimize Si INTAN as an effective digital complaint management instrument in supporting the implementation of SPMB in West Nusa Tenggara Province.